Level Kognitif Taksonomi Bloom pada Soal Mata Pelajaran Bahasa Indonesia - Cressa, Jerri; Mukhlis, Muhammad (UIR Press, 2023)
This study aims to determine the percentage of the cognitive level of Bloom's Taxonomy in the even semester final exam questions for class X Indonesian at SMKN 2 Pekanbaru with a total of 50 multiple choice questions. This type of research uses a qualitative approach with descriptive methods, in which the results of the research will be described, analyzed, interpreted, and concluded. Data collection techniques used are documentation techniques, and hermeneutic. The data analysis technique used is content analysis. The results showed that the percentage for level 1 (knowledge and understanding) or LOTS percentage found was 56% with the cognitive remembering (C1) category of 16%, and understanding (C2) of 40%. Furthermore, level 2 (application) or MOTS percentage found is 6% with the cognitive category of applying (C3) of 6%. While level 3 (application) or HOTS percentage found was 38% with the category of cognitive analyzing (C4) of 36%, evaluating (C5) of 2%, but no level questions were found in the cognitive category of creating (C6).